Potential of organic Rankine cycle technology in India: Working fluid selection and feasibility study - Sarkar J.; Bhattacharyya S. (My University, 2025)
India has great potential to employ the ORC (organic Rankine cycle) technology for conversion of low temperature waste heat and renewable energy. In this study, available waste heat and relevant renewable heat sources in India are reviewed and suitable working fluids for ORC have been selected based on operational, environmental and safety criteria. A feasibility study and comparison of selected fluids for ORC is also presented for Indian climates along with discussions on component, operation and cost related aspects. A comprehensive review on available heat sources and sinks shows that India has plenty of waste heat and renewable energy sources for electricity generation by means of ORC; however, condenser operation may be challenging due to wide ambient temperature variation. Appropriate performance comparison among selected working fluids shows that ammonia is the best fluid in terms of net power generation and compactness of turbo-machineries, whereas n-Pentane is the best fluid in terms of thermal efficiency and heat exchanger compactness. Both are recommended as working fluids for ORC installations in India. The study reveals that there is a great opportunity to employ this technology in India provided we have to overcome some challenges related to component selection, finance and maintenance. © 2015 Elsevier Ltd.